SYSTEMATIC LITERATURE REVIEW: ANALYSIS OF THE APPLICATION OF BLOCKCHAIN ​​TECHNOLOGY IN TRACKING FINANCIAL TRANSACTIONS IN MSMEs - Fachrudy Asj’ari (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2026)
Micro, Small, and Medium Enterprises (MSMEs) face significant challenges in financial management, particularly related to transparency and reliability of transaction tracking, which hinders their access to formal financing. This study aims to synthesize scientific evidence regarding the application of blockchain technology in improving the tracking and transparency of financial transactions in MSMEs. Using a Systematic Literature Review (SLR) or Wide Research approach with the PICOS framework, ten (10) relevant primary studies (original research papers) were identified, selected, and analyzed. The synthesis results show that blockchain significantly improves transparency, data security, and cost efficiency in tracking MSME transactions, and has great potential in increasing access to financing through a more credible credit scoring system. However, the main challenges lie in the high initial implementation costs and the need for digital literacy. This study provides a clear roadmap for researchers, policymakers, and practitioners to optimize the adoption of blockchain technology in the MSME sector.